Pendidikan dan Tujuan Pendidikan Islam dalam Persfektif Filsafat Pendidikan Islam - Sri Mulyani; Latifatul Azizah; Binti Khoir Faridi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This article applies a descriptive qualitative method by applying library research techniques in data collection. The results of this research are that philosophy is one of the foundations in education. The philosophy of Islamic education is a science that looks at the process of teachers educating students so that they can develop from not knowing to becoming knowledgeable so as to form quality students with all the potential that exists within them. Humans cannot live alone in their lives. The research explains how education and educational goals are in Islamic educational philosophy.